Hannah Arendt : (im)possibilidades de superação da banalização da violência - Prieto, Amélia Cristina Silva Machado (2012)
This dissertation proposes to instigate the debate on the issues of the violence and its banalization in our society in the light of the reflections raised by Hannah Arendt. Initially, we introduced basic concepts for understanding the work of Arendt, since the period of greek tradition to the present society. Then we present the Arendt s discussion on the banalization of violence and alienation, from a historical review in search of the origins of the ills of the contemporary society, and the philosophical analysis of its difficulties and its consequences. Finally we seek to contextualize the theoretical legacy of Hannah Arendt with current debates in our society, in order to show the restoration of the dignity of politics and the recovery of public space as possible solutions to these problems.